2003
DOI: 10.1023/b:catb.0000007023.85139.c5
|View full text |Cite
|
Sign up to set email alerts
|

Use of Banked Tissue in Plastic Surgery

Abstract: The availability of safe and reliable, banked tissues in India has enabled the use of human bone allografts as a viable alternative to autografts in reconstructive surgery. Lyophilised, irradiated bone grafts were used in 2 cases of rhinoplasty, a case of hemifacial atrophy, and as a chin implant.In the patient with revision rhinoplasty the rib graft was resorbed. The patient with hemifacial atrophy developed seroma and infection in the zygomatic and infraorbital area and the rib graft had to be removed. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 18 publications
0
20
0
3
Order By: Relevance
“…They showed that burn wound coverage by amnion significantly decreased the bacterial contamination in infected rats. Nowadays, amniotic membranes are efficiently used as allografts for treating skin burns; open and non-healing ulcers; pressure sores; and surgical, infected and traumatic wounds; as well as skin graft donor sites (Andonovska et al, 2008;Branski et al, 2008;Gajiwala and Gajiwala, 2004;Gajiwala and Lobo Gajiwala, 2003;Kesting et al, 2008;Ravishanker et al, 2003;Singh et al, 2004;Singh et al, 2008;Singh et al, 2007;Toda et al, 2007;Wilshaw et al, 2008).…”
Section: Clinical Applications Of Human Amnionmentioning
confidence: 99%
“…They showed that burn wound coverage by amnion significantly decreased the bacterial contamination in infected rats. Nowadays, amniotic membranes are efficiently used as allografts for treating skin burns; open and non-healing ulcers; pressure sores; and surgical, infected and traumatic wounds; as well as skin graft donor sites (Andonovska et al, 2008;Branski et al, 2008;Gajiwala and Gajiwala, 2004;Gajiwala and Lobo Gajiwala, 2003;Kesting et al, 2008;Ravishanker et al, 2003;Singh et al, 2004;Singh et al, 2008;Singh et al, 2007;Toda et al, 2007;Wilshaw et al, 2008).…”
Section: Clinical Applications Of Human Amnionmentioning
confidence: 99%
“…Moreover, autologous bone grafts have the drawback of requiring secondary surgery for autograft retrieval, with increased operation time and anaesthesia, and donor site morbidity [1]. On the other hand, biomaterials are good but expensive, and may become infected at a later date [2]. So, the use of homograft bone provides a reasonable alternative to meet the need for graft material [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, biomaterials are good but expensive, and may become infected at a later date [2]. So, the use of homograft bone provides a reasonable alternative to meet the need for graft material [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, autologous bone grafts have the drawback of a secondary surgery field for autograft retrieval, with increased operation time and anesthesia, and donor site morbidity. On the other hand, biomaterials are good but expensive, and may extrude at a later date (Gajiwala and Lobo Gajiwala 2003). So, the use of homologue bone provides a reasonable alternative to meet the need for graft material (Vargel et al 2004).…”
Section: Introductionmentioning
confidence: 99%